Using Artificial Neural Networks for Solving Forensic Handwriting Examination Problems: Foreign Experience Analysis - V. A. Mishchuk (Теория и практика судебной экспертизы)
This paper studies the foreign experience of artificial neural networks (ANN) application in forensic handwriting examination. Given the active ANN implementation in various areas of public life, greater attention is paid to the integration of this technology into forensic activities. According to the opinion of a number of scientists and lawyers the issue of applying neural networks to forensic handwriting examination is particularly acute as they can significantly improve the objectivity of handwriting examinations.The article gives a brief overview of history and current developments in computer technology use for handwriting examination as well as the connection and mutual influence of forensics and biometrics in this field which is particularly characteristic of foreign practice of forensic handwriting examination. Furthermore, the author presents examples of successful projects and experiments demonstrating effective use of neural networks to identify and verify an individual by his handwriting. The paper also discusses the prospects of this field and identifies the key challenges hindering, in the author’s opinion, the ANN integration in forensic handwriting examination.